Determinants and Prediction Equations of Six-Minute Walk Test Distance Immediately After Cardiac Surgery - Radi, Basuni; Ambari, Ade Meidian; Dwiputra, Bambang; Intan, Ryan Enast; Triangto, Kevin; Santoso, Anwar; Setianto, Budhi (Frontiers in Cardiovascular Medicine, 2021)
Background: To date, there are no reference for six-minute walk test (6-MWT) distance immediately after cardiac surgery. Therefore, this study aimed to identify the determinants and to generate equations for prediction reference of 6-MWT distance in patients immediately after cardiac surgery. Methods: This is a cross-sectional study of the 6-MWT prior to participation in the cardiac rehabilitation (CR) program of patients after coronary artery bypass surgery (CABG) or valve surgery. The 6-MWT were carried out in a gymnasium prior to CR program immediately after the cardiac surgery. Available demographic and clinical data of patients were analyzed to identify the clinical determinants of 6-WMT distance. Results: This study obtained and analyzed the data of 1509 patients after CABG and 632 patients after valve surgery. The 6-MWT distance of all patients was 321.5±73.2 meters, (60 - 577). Distance was longer in valve surgery group rather than those of patients in CABG group (327.75±70.5 vs 313.59±75.8 meters, p<0.001). Determinants which significantly influences the 6-MWT distance in CABG group were age, gender, diabetes, atrial fibrillation, and body height. Whereas in valve surgery group were age, gender and atrial fibrillation. The multivariate regression models generated two formulas using the identified clinical determinants for patients after CABG: 6-MWT distance (meter) = 212.57 + 30.47 (if male gender) – 1.62 (age in year) + 1.09 (body height in cm) – 12.68 (if diabetes) – 28.36 (if atrial fibrillation), and for patients after valve surgery with the formula of: 6MWT distance (meter) = 371.05 + 37.98 (if male gender) - 1.36 (Age in year) – 10.61 (if atrial fibrillation). Conclusion: This study had identified several determinants for the 6-MWT distance, and successively generated two reference equations for predicting 6-MWT distance in patients after CABG and valve surgery.